Cylindroma of the Breast: A Rare Differential for Breast Cancer on Core Biopsies, Case Report and Review of Literature - Dre Steinwehr MD; Toshi Ghosh MD; Michael Bouton MD (SAGE Publishing, 2024)
Breast cancers of either ductal or lobular pathology make up the vast majority of breast malignancies. Other cancers occur rarely in the breast. Benign pathology can at times mimic breast cancers on imaging and initial needle biopsies. We report a rare breast pathology of cylindroma. Cylindromas are usually benign, rare dermatologic lesions most commonly associated with head or neck locations. They more commonly occur as sporadic and solitary masses. Less commonly is an autosomal-dominant multi-centric form of this disease. Malignant cylindromas are very rare. We present a patient with findings of a cylindroma of the breast after excision. This was initially felt to be concerning for breast cancer on imaging and core biopsy. Treatment of cylindromas of the breast is excision. Sentinel lymph node dissection is not indicated, nor are adjuvant therapies when identified in the breast. This lesion needs to be included in the differential diagnosis for breast cancer. If cylindromas can be accurately diagnosed preoperatively, this would negate the need for consideration of axillary nodal surgery and adjuvant therapies.